INDUSTRIAL REVOLUTION 4.0 ORIENTED IPS LEARNING THROUGH INFUSING BLENDED LEARNING IN JUNIOR HIGH SCHOOLS - Sujarwo; Tubagus Ali Rachman (Journal Civics And Social Studies, 2021)
The aim of this research is to develop a learning model that suits the demands of the times in the era of industrial revolution 4.0. which has had an impact on shifting the paradigm of learning patterns, namely learning patterns that use technology versus learning that does not use technology, as well as differences in the concept of learning in the classroom (classroom setting) to digital learning that does not always have to be in the classroom. This research uses a Research and Development approach by grouping it into three stages, namely: 1) Preliminary Study, 2) Program planning and preparation and 3) program trial. This research was carried out at SMP Negeri 92 Jakarta, in the even semester of the 2019/2020 academic year. The sampling technique in this research was purposive sampling by taking a sample of one study group in class VII of SMP Negeri 92 Jakarta. The results of this research developed an infusing blended learning model carried out using a cooperative and contextual learning model with a scientific approach and integrating or incorporating digital information technology into learning using Google Classroom and Kahoot! succeeded in improving participant learning outcomes and student learning activeness. So it can be concluded that the use of the infusing blended learning model by integrating Google Classroom and Kahoot! Social studies learning is in accordance with the industrial revolution 4.0 which is characterized by the use of internet-based information technology and can be used as an alternative for teachers in carrying out learning innovations.